MUSCLE MRI SEGMENTATION USING RANDOM WALKER METHOD - A. V. Shukelovich; E. V. Snezhko; V. A. Kovalev; A. V. Tuzikov (Informatika)
A technique of marker set construction for muscle MRI segmentation using random walker approach is introduced. The possibility of clinician’s manual labor amount reduction and random walker algorithm optimization is studied.